THU0513 Impaired Recognition of Porphyromonas Gingivalis in Rheumatoid Arthritis Patients. (10th June 2014) - Santegoets, K.; Wenink, M.; Braga, F.; Cossu, M.; Lamers-Karnebeek, F.; van Riel, P.; Sturm, P.; van den Berg, W.; Radstake, T.
Abstract : Background: The prevalence of periodontitis is increased in patients with rheumatoid arthritis (RA) and the severity of periodontitis can affect the level of arthritis. Porphyromonas gingivalis is one of the main bacteria involved in periodontitis and DNA from this bacterium can be found in RA synovial tissue. Furthermore, P. gingivalis is the only known bacterium that can citrullinate proteins, the target of autoantibodies in many RA patients. Therefore, P. gingivalis is a prime candidate for investigation in RA pathogenesis. Objectives: Our aim was to determine possible differences in the innate immune response against P. gingivalis between healthy controls and RA patients. Methods: Monocyte-derived dendritic cells (DCs) from healthy controls, RA and psoriatic arthritis (PsA) patients were stimulated with P. gingivalis, a range of other bacteria and TLR agonists. Cytokine production was determined using a Luminex-based assay and blocking studies were performed to determine which receptors were involved in differential recognition of P. gingivalis . Cytokine production was also determined in peripheral blood mononuclear cell (PBMC) cultures stimulated with P. gingivalis . Results: RA DCs produced markedly less TNFα, IL-12p70 and IL-8 as compared to healthy controls upon stimulation with P. gingivalis, but not with the other bacteria tested. In sharp contrast, DCs from PsA patients did not differ from healthy controls, suggesting a RA-specific deregulated response to P. gingivalis . Cytokine production upon P. gingivalis stimulation did not correlate with clinical disease characteristics. The difference between RA patients and controls was abolished when complement receptor 3 was blocked. In PBMC cultures, interferon gamma induction by P. gingivalis was also significantly reduced in RA patients. Conclusions: Immune cells from RA patients display a marked diminished response to P. gingivalis . This could result in prolonged survival of P. gingivalis and an increased oral bacterial burden in RA patients, possibly driving autoantibody formation and the characteristic self-perpetuating loop of chronic inflammation. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3229